Compartment Syndrome of the Hand Induced by Peripherally Extravasated Phenylephrine. (January 2021) - Fisher, Alec H.; Jarrett, Nicole J.
Background: Compartment syndrome of the hand is a rare and devastating complication of peripheral intravenous extravasation. With changes in critical care research, vasoactive medications are now more frequently administered through peripheral lines in the acute setting.Methods: We present the case of a patient diagnosed with compartment syndrome of the hand secondary to phenylephrine extravasation in the setting of hypovolemic shock.Results: The use of fasciotomy compartment release and intraoperative phentolamine resulted in significant improvement in tissue perfusion postoperatively.Conclusion: With incraesed incidence of peripherally administered vasoactive medications, the hand surgeon should be aware of potential complications and treatment of compartment syndrome with urgent fasciotomy and phentolamine administration.